2018
DOI: 10.1186/s12889-018-5946-z
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal washing and lubrication among female sex workers in the Mexico-US border region: implications for the development of vaginal PrEP for HIV prevention

Abstract: BackgroundTo assess the potential acceptability and inform the development of behaviorally-congruent vaginal douche- or gel-based HIV pre-exposure prophylaxis (PrEP) products, we examined vaginal washing and lubrication practices among female sex workers (FSWs) in Tijuana and Ciudad Juarez, two northern Mexico cities bordering the United States (US).MethodsTwo hundred and ninety-five HIV-negative FSWs (145 Tijuana; 150 Ciudad Juarez) enrolled in a behavioral HIV prevention intervention trial completed surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…35 A study that examined vaginal washing and vaginal lubrication among FSWs in Tijuana and Ciudad Juarez, Mexico documented moderate (39%) and high (54%) prevalences of vaginal washing and lubrication in the past month, respectively, suggesting that vaginal PrEP products formulated as douches or gels may be acceptable HIV prevention methods to many FSWs in the Mexico-US border region. 42 The authors of the study also identified several predictors of each vaginal practice, providing insight into the characteristics of FSWs for whom these vaginal PrEP products may be most acceptable. 42 Lifestyle factors, such as substance use, can affect PrEP adherence.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…35 A study that examined vaginal washing and vaginal lubrication among FSWs in Tijuana and Ciudad Juarez, Mexico documented moderate (39%) and high (54%) prevalences of vaginal washing and lubrication in the past month, respectively, suggesting that vaginal PrEP products formulated as douches or gels may be acceptable HIV prevention methods to many FSWs in the Mexico-US border region. 42 The authors of the study also identified several predictors of each vaginal practice, providing insight into the characteristics of FSWs for whom these vaginal PrEP products may be most acceptable. 42 Lifestyle factors, such as substance use, can affect PrEP adherence.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…42 The authors of the study also identified several predictors of each vaginal practice, providing insight into the characteristics of FSWs for whom these vaginal PrEP products may be most acceptable. 42 Lifestyle factors, such as substance use, can affect PrEP adherence. One study found that combined use of illicit drugs and tenofovir disoproxil fumarate can be nephrotoxic.…”
Section: Lifestyle Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…For other innovative biomedical HIV prevention tools, such as oral PrEP and vaginal microbicides, the development of behaviourally congruent products can play a primary role in uptake and adherence [94,129,130]. Overall, the studies described demonstrate that improving comprehensive HIV prevention packages with innovative tools means integrating sexual and reproductive health services, multi-purpose prevention products, and awareness of structural determinants experienced by sex workers that affect engagement in care.…”
Section: Other Innovationsmentioning
confidence: 96%
“…In a previous study, between 4 and 18% of women reported removing the ring either during menses or for periodic cleaning (Montgomery et al, 2012). Application of a variety of different substances to the vagina for general health, cleaning or sexual function has also been reported in different populations (Gafos et al, 2010;Low et al, 2011;Martin Hilber et al, 2010;Pines et al, 2018). Further, previous clinical studies have observed ring discolouration following use (Spence et al, 2016).…”
Section: Introductionmentioning
confidence: 98%